The impact of administrative empowerment on employee performance: A field study in pharmaceutical companies listed on Amman stock exchange - Alqudah, Enas Hani (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to investigate the effect of managerial empowerment with its dimensions (authority delegation, autonomy, motivation) on the performance of employees in the pharmaceutical industry companies at Amman Stock Exchange from the view of managers and employees on these companies. The study assumed that there is no a significant relationship between the dimensions of managerial empowerment and the performance of employees at a level of statistical significance (α <0.05). SPSS was used to find the arithmetic means, standard deviations and variances. The study sample is consisted of 200 questionnaires, 170 of the questionnaires were found valid to analyze with a percentage 85. 5%. The questionnaire is consisted of 30 items. The study used the descriptive analytical approach and the validity and reliability of the study instrument is verified. The simple regression was used to test the study hypotheses. The results of the study showed a positive effect of managerial empowerment and its dimensions at a significant level (a <0.05) on the performance of the employees in the following statements: - There is a positive effect of authority delegation on the performance of employees with a coefficient of determination0. 388 - There is a positive effect of autonomy on the performance of employees with a coefficient of determination0. 591 - There is a positive effect of motivation on the performance of employees with a coefficient of determination0. 70; this variable recorded the highest value. Based on the results of the study, the researcher recommended the importance of activating the managerial empowerment and its dimensions and providing more authority delegation to employees in performing their duties within their specializations and more autonomy to motivate them to perform their works, which is reflected positively on their performance at Jordanian companies.